Analytical study of the predictive value of achievement as a function of the achieved velocity of linear and angular body parts for the stage of throwing and starting position and javelin throwing accomplishment - Majeed Salall, Mohammed (International Journal of Psychosocial Rehabilitation, 2025)
The importance of the research came through emphasizing an important variable, which is the speed the shooter acquires for his body parts during approaching and speed in the final stage of throwing. In it, to identify the influencing relationship between the values of the achieved velocity of the body parts (linear and angular) to place the throwing effectiveness of the javelin and the completion of the research sample, the researchers used the descriptive approach by the method of the relational and surveying relationship to suit the nature of the research. The research was carried out in an intentional way, and the number was six ) players from the Diyala Club for the sports season (2018-2019), and they were under 18 years old. The research procedures included conducting imaging and extracting the variables that included the linear velocity of the body parts of the hip, shoulder, elbow, and spear and the angular velocity of each (the stem and the aiming arm). The field application was conducted to conduct the main experiment on the research sample on Tuesday, 10/12/2019. In light of the achieved results, the results showed a high correlation and impact force between the achieved speed of body parts (linear and angular) for the throwing phase and the javelin throw for the youth.